Psychometrics properties of a questionnaire on the attitudes of general practitioners towards mental health (MAPSAM-14) - Moreno Küstner, Berta; Bordallo Aragon, Antonio; Sepúlveda Muñoz, Jesús (Anales de Psicología / Annals of Psychology, 2018)
Background: The aim of this study is to adapt and analyze the psychometric properties of a questionnaire on the perceptions of general practitioners towards mental health. Method: This is a descriptive cross-sectional, observational study. A total of 145 general practitioners from the reference area of Malaga Regional Hospital answered this 25-item questionnaire; a factorial analysis was then conducted and its internal consistency reliability was tested. Results: The adequacy of sampling and sphericity were satisfactorily met. Three dimensions measured by 14 items were found in the factorial analysis explaining 55.1% of its variance: the MAPSAM-14 questionnaire. Conclusions: This questionnaire may be a proper tool with which to determine the satisfaction of general practitioners in relation to mental health services, their beliefs and stigma towards mental illness and their level of training in the field of schizophrenia and related disorders.